The strategic role of external sustainability assessment in the food value chain - Müller, Philipp (2014)
Purpose: This research seeks to shed more light on how external sustainability assessment in the food value chain could achieve a more significant strategic impact, as most organizations fail to implement sustainability measures beyond marketing efforts. A model is proposed that aims to clarify the understanding of the process, including the influence of the actors and the way they are affected. Design/methodology/approach: The topic is initially approached rather broadly from the perspective of performance measurement and management due to a lack of relevant literature, creating the link to sustainability and its assessment in a second step. Nine essential themes are developed from the theory and their applicability in the relevant field tested through two case studies. Findings: The identified themes are all relevant in the context of sustainability assessment in the food value chain and furthermore show a strong interconnectivity. This interconnectivity is particularly complicated by the externalization of the assessment and can lead to conflicts, which then limits the success and the strategic opportunities of the assessments. Research Limitations: Selecting a case study approach, this research cannot claim general applicability, particularly since the topic is relatively unexplored. Furthermore the primary data had a strong focus on experiences in western countries. Practical Implications: Due to the complexity of sustainability assessment, involved actors need to cooperate closely and share their expertise. The developed model can help to create awareness regarding this aspect, and sensitize and prepare organizations for potential areas of conflict, facilitating a more efficient collaboration. Originality/value: This research makes an ambitious attempt to view sustainability assessment as a modern form of performance measurement and management. In doing so it demonstrates that there are solutions for organizations that wish to manage sustainability on a strategic level.